2016
DOI: 10.1074/jbc.m116.735258
|View full text |Cite
|
Sign up to set email alerts
|

Asn347 Glycosylation of Corticosteroid-binding Globulin Fine-tunes the Host Immune Response by Modulating Proteolysis by Pseudomonas aeruginosa and Neutrophil Elastase

Abstract: Corticosteroid-binding globulin (CBG) delivers anti-inflammatory cortisol to inflamed tissues upon elastase-based proteolysis of the exposed reactive center loop (RCL).glycan features are modulating the RCL digestion efficiencies by NE/PAE. Finally, high concentrations of cortisol showed weak bacteriostatic effects toward virulent P. aeruginosa, which may explain the low RCL potency of the abundantly secreted PAE during host infection. In conclusion, site-specific CBG N-glycosylation regulates the bioavailabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…36,37 Important mechanistic questions about the CBG cleavage phenomenon remain including the influence of CBG genetics, known to influence cleavage and a potential host factor in septic shock, as well as the effect of glycosylation on RCL function. 38,39 We have not related our measures of CBG cleavage to organism in the sepsis patients, but our previous study of patients referred for blood culture found that organism or blood culture positivity (generally around 50% or less in septic shock) did not relate to extent of cleavage. 37 Multiple factors contribute to mortality in the critically ill, including comorbid conditions and primary diagnoses; those with nonseptic critical illness were a heterogenous group.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…36,37 Important mechanistic questions about the CBG cleavage phenomenon remain including the influence of CBG genetics, known to influence cleavage and a potential host factor in septic shock, as well as the effect of glycosylation on RCL function. 38,39 We have not related our measures of CBG cleavage to organism in the sepsis patients, but our previous study of patients referred for blood culture found that organism or blood culture positivity (generally around 50% or less in septic shock) did not relate to extent of cleavage. 37 Multiple factors contribute to mortality in the critically ill, including comorbid conditions and primary diagnoses; those with nonseptic critical illness were a heterogenous group.…”
Section: Discussionmentioning
confidence: 95%
“…The second study involved a patient group with a higher mortality rate: 43% hydrocortisone/fludrocortisone and 49% placebo vs 28% hydrocortisone and 29% placebo in the first study. Important mechanistic questions about the CBG cleavage phenomenon remain including the influence of CBG genetics, known to influence cleavage and a potential host factor in septic shock, as well as the effect of glycosylation on RCL function 38,39. Important mechanistic questions about the CBG cleavage phenomenon remain including the influence of CBG genetics, known to influence cleavage and a potential host factor in septic shock, as well as the effect of glycosylation on RCL function 38,39.…”
mentioning
confidence: 99%
“…Upon arrival, HNE was highly pure (Ͼ95%) and displayed full structural and functional integrity (i.e. showed high enzyme activity on various substrates) as assessed by SDS-PAGE (Invitrogen, Australia) and immunoblotting with rabbit anti-HNE (1:500, kind gift from Prof Niels Borregaard, University of Copenhagen, Denmark) and by its ability to rapidly cleave CBG (24). HNE was stored in a soluble form at 1.9 g/l in 50 mM sodium acetate and 600 mM sodium chloride buffer, pH 5.5 at 4°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…In the extracellular environment, HNE serves multiple protective and regulatory roles within the innate immune system. For example, HNE inhibits the growth of Gram-negative bacteria such as Pseudomonas aeruginosa in the airways (23) and facilitates the release of anti-inflammatory cortisol from corticosteroid binding globulin (CBG) at inflammatory sites (24). However, because of its high enzymatic activity, excessive secretion of HNE can damage the connective tissues of the lungs by causing proteolytic degradation of elastin, fibronectin and collagen, as commonly observed in chronic obstructive pulmonary disease and in chronic inflammation (25).…”
mentioning
confidence: 99%
“…As an example the K M = 1.4 · 10 5 nM and the catalytic constant k cat = 1.0 · 10 3 min −1 for elastase's cleavage of methoxysuccinyl-Ala-Ala-Pro-Val-4-nitroanilide [73]. However, CBG as opposed to methoxysuccinyl-Ala-Ala-Pro-Val-4-nitroanilide and a lot of other elastase substrates after cleavage does not inhibit the further activity of elastase and Hammond et al [74] describe the cleavage of CBG by elastase as extremely efficient [74] and Sumer-Bayraktar et al [75] the reaction as fast.…”
Section: Elastase Activitymentioning
confidence: 99%